2015
DOI: 10.1007/s00253-015-6882-9
|View full text |Cite
|
Sign up to set email alerts
|

Selective elimination of bacterial faecal indicators in the Schmutzdecke of slow sand filtration columns

Abstract: Slow sand filtration (SSF) is an effective low-tech water treatment method for pathogen and particle removal. Yet despite its application for centuries, it has been uncertain to which extent pathogenic microbes are removed by mechanical filtration or due to ecological interactions such as grazing and competition for nutrients. In this study, we quantified the removal of bacterial faecal indicators, Escherichia coli and Enterococcus faecalis, from secondary effluent of a wastewater treatment plant and analysed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
24
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 41 publications
7
24
0
1
Order By: Relevance
“…Accordingly, no significant effect of the assumed higher adsorption capacity of bacteria on biochar could be observed over the whole experimental period of 70 days. Due to the high OLR of the AnBFs, which was notably higher than in comparable studies 7,8,18,19 , it can be assumed that the adsorption capacity of biochar was exhausted in an early stage of our experiment. This is supported by the fact that the main removal of E. coli in the AnBFs took place within the schmutzdecke.…”
Section: Resultsmentioning
confidence: 76%
See 1 more Smart Citation
“…Accordingly, no significant effect of the assumed higher adsorption capacity of bacteria on biochar could be observed over the whole experimental period of 70 days. Due to the high OLR of the AnBFs, which was notably higher than in comparable studies 7,8,18,19 , it can be assumed that the adsorption capacity of biochar was exhausted in an early stage of our experiment. This is supported by the fact that the main removal of E. coli in the AnBFs took place within the schmutzdecke.…”
Section: Resultsmentioning
confidence: 76%
“…Its suitability as tertiary treatment option for secondary effluents on municipal wastewater treatment plants (WWTPs) to reach an appropriate quality for safe irrigation water with a relatively high hydraulic loading rate (HLR) of more than 0.05 m•h −1 was confirmed by several studies. For instance, Langenbach et al 7 reported an average reduction of fecal indicator bacteria (FIB) of 1.95 to 2.46 log-units, while Pfannes et al 8 found an elimination between 1.58 and 2.26 log-units. For coliforms, a reduction of 1.4 to 2.0 log-units was reported by Ellis 9 and for total coliforms a removal between 0.68 and 2.0 log-units 10,11 .…”
mentioning
confidence: 99%
“…They found that the eukaryotic community was dominated by Cercozoa (Ebridd-type protists). Ciliate protozoa, green microalgae, stramenopiles, amoeboid protozoa, and fungi in the Phylum Ascomycota and the deep-branching Chytridiomycota were also detected [9]. The images of bacteria in the schmutzdecke taken by a scanning electron microscope (SEM) is shown in Fig.…”
Section: Results Based On Bio-slow Sand Filtrationmentioning
confidence: 99%
“…Both sand filtration and bank filtration were studied extensively in the past regarding the rejection of potential microbiological hazards. In slow sand filters, 1-3 log removal (90-99.9%) was observed by different authors, both by colony counting and other methods [7,8]. RBF was reported to be capable of 2-5 log reduction for pathogen indicator parameters, such as E. coli and coliforms [9,10].…”
mentioning
confidence: 99%
“…The flow velocity in slow sand filters (1-50 cm/h) [3,4] are comparable with those documented for BF sites (0.1-50 cm/h) [5,6].Both sand filtration and bank filtration were studied extensively in the past regarding the rejection of potential microbiological hazards. In slow sand filters, 1-3 log removal (90-99.9%) was observed by different authors, both by colony counting and other methods [7,8]. RBF was reported to be capable of 2-5 log reduction for pathogen indicator parameters, such as E. coli and coliforms [9,10].Consequently, with respect to the importance of the first few centimeters of the top layer, both RBF and MAR in general have some analogy with slow sand filtration and cake filtration.…”
mentioning
confidence: 99%